'WE DON'T ALL LOOK ALIKE'. (29th December 2014) - Byrd, W. Carson; Brunn-Bevel, Rachelle J.; Sexton, Parker R.
Abstract The examination of student group performance is a constant need as American higher education continues to expand and become more racially and ethnically diverse. Recent scholarship on the academic performance of Black students at elite colleges and universities has glossed over possible disparities among these students, particularly among different immigrant groups. The current study clarifies these differences in academic performance by examining four Black student groups at elite colleges and universities in the United States: native Blacks, Black immigrants from Africa, Black immigrants from the Caribbean and Latin America, and Black immigrants from other parts of the globe. The analyses point to many similarities and differences among the four Black student groups in their characteristics and influences on their academic performance in college such as gender, precollege friendships, high school academic preparation, college major, and closeness to Whites and Blacks. Additionally, this study found evidence of possible colorism among Black students at elite colleges.